Organophosphate flame retardants and immunotoxicity: An integrated bibliometric and systematic review of epidemiological and mechanistic evidence - Chengyue Ma; Yuhao Zhong; Xiaowen Huang; Minghui Li; Jinsong Zhao; Chunji Wang; Fang Zhang; Yue Jia; Yuxin Jiang; Yingli Li; Meiling Shi; Shuqi Chen; et al. (Journal of Environmental Sciences, 2026)

Aneuploid gametes produced by triploid Populus ‘Beilinxiongzhu 1#’ transmit higher paternal heterozygosity to progeny - Yaru Sang; Yunyun Xie; Yifan Zhao; Bo Kong; Dawei Cheng; Liang Li; Lexun Ma; Jiahua Du; Meiling Long; Dongliang Cao; Zhang Huajian; Lao Huiqi; et al. (Tree Genetics & Genomes, 2026)

Hydrangea-derived nitrogen-doped carbon dots: A dual-purpose platform for on-site chlortetracycline detection and time-limited anti-counterfeiting - Meiling Long; Decheng Peng; Jun Yang; Shaogui Wu (Analytica Chimica Acta, 2026)

Tetrahydrocurcumin for Major Depressive Disorder with Therapeutic Potential and Mechanistic Insights from Clinical and Preclinical Studies - Ying Guo; Jianping Xie; Haiyun Luo; Yun Yuan; Fang Long; Jingyuan Meng; Hui Tan; Yuanping Li; Bibo Cai; Meiling Chen; Liyan Yang; Jingmei Zhong; et al. (Molecular Neurobiology, 2026)

Integrating network pharmacology, molecular docking, and bioinformatics to explore the mechanism of sparganii rhizoma in the treatment of laryngeal cancer - Meiling Zheng; Rui Zhang; Xinxing Yang; Feiyan Wang; Xiaodi Guo; Long Li; Jin Wang; Yajun Shi; Shan Miao; Wei Quan; Shanbo Ma; Xiaopeng Shi (Molecular Diversity, 2025)

2,2',4,4'-tetrabromodiphenyl ether (BDE-47) induces early hearing loss in guinea pigs via activating AhR to trigger mitochondrial and endoplasmic reticulum stress-regulated autophagy - Jie Tang; Li Zhang; Yujia Yang; Chunji Wang; Fang Zhang; Muxin Yu; Nenghua Zhang; Guangtao Xu; Bo Hu; Meiling Shi; Long Xu (Archives of Toxicology, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Different activation of STAT1 and STAT2 phosphorylation by IFNc, IFNd, and IFNh in tilapia - Qingqing Wen; Shaoshuai Tang; Jingyi Mo; Meiling Zhang; Meng Long; Yishan Lu; Zhen Gan (Fish & Shellfish Immunology, 2024)

Evaluation of magnetic calcium silicate hydrate derived from halloysite clay for efficient phosphate capture - Debin Jiang; Xue Long; Meiling Xiang; Xiantian Gan; Qinghong Pu; Yu Chen; Ning Qi; Xiaoping Wang (Journal of Environmental Chemical Engineering, 2024)

Catalytic destruction of chlorobenzene over K-OMS-2: Inhibition of high toxic byproducts via phosphate modification - Yunpeng Long; Jiajia Liu; Meiling Chen; Renna Li; Xiaole Weng; Zhongbiao Wu (Journal of Environmental Sciences, 2023)

Diversity and Disease: The Effects of Coral Diversity on Prevalence and Impacts of Stony Coral Tissue Loss Disease in Saint Thomas, U.S. Virgin Islands - Sophia V. Costa; Stephanie J. Hibberts; Danielle A. Olive; Kayla A. Budd; Alexys E. Long; Sonora S. Meiling; Madyson B. Miller; Kelsey M. Vaughn; Claudia I. Carrión; Maksym B. Cohen; Annie E. Savage; Matthew F. Souza; et al. (Frontiers in Marine Science, 2021)
Stony coral tissue loss disease (SCTLD) was first observed in St. Thomas, U.S. Virgin Islands (USVI) in January 2019. This disease affects at least 20 scleractinian coral species; however, it is not well understood how reef diversity affects its spread or its impacts on reef ecosystems. With a large number of susceptible species, SCTLD may not follow the diversity-disease hypothesis, which proposes that high species diversity is negatively correlated with disease prevalence. Instead, SCTLD may have a higher prevalence and a greater impact on reefs with higher coral diversity. To test this, in 2020 we resampled 54 sites around St. Thomas previously surveyed in 2017 or 2019 by the National Oceanic and Atmospheric Administration National Coral Reef Monitoring Program. These sites represented a variety of species diversity values [categorized into poor (<12 spp. rich.) and rich (≥12 spp. rich.)] in multiple disease zones (Endemic: disease present ≥ 9 months; Epidemic: disease present 2–6 months; Control and Emergent: disease present no disease/<2 months). We hypothesized that, contrary to the diversity-disease hypothesis, sites with high species diversity (as measured by species richness or Simpson’s index) would have higher disease prevalence within the epidemic zone, and that high species diversity sites would have a greater impact from disease within the endemic zone. Results indicated a significant positive relationship between disease prevalence and diversity in the epidemic zone, and a similar trend in the endemic zones. Additionally, a negative relationship was seen between pre-outbreak diversity and loss of diversity and coral cover within the endemic zone. This supports the hypothesis that higher diversity predicts greater disease impact and suggests that SCTLD does not follow the diversity-disease hypothesis. Within the epidemic zone, the species with the highest SCTLD prevalence were Dendrogyra cylindrus , Colpophyllia natans , and Meandrina meandrites , while in the endemic zone, Diploria labyrinthiformis , Pseudodiploria strigosa , Montastraea cavernosa , and Siderastrea siderea had the highest SCTLD prevalence. Understanding the relationship between species diversity and SCTLD will help managers predict the most vulnerable reefs, which should be prioritized within the USVI and greater Caribbean region.

Characterization of Post-traumatic Stress Disorder Using Resting-State fMRI with a Multi-level Parametric Classification Approach - Feng Liu; Bing Xie; Yifeng Wang; Wenbin Guo; Jean-Paul Fouche; Zhiliang Long; Wenqin Wang; Heng Chen; Meiling Li; Xujun Duan; Jiang Zhang; Mingguo Qiu; et al. (Brain Topography, 2015)